2008
DOI: 10.1158/1055-9965.epi-07-2803
|View full text |Cite
|
Sign up to set email alerts
|

A 22-year Prospective Study of Fish,n-3 Fatty Acid Intake, and Colorectal Cancer Risk in Men

Abstract: Background: Fish is the main dietary source of longchain n-3 fatty acids, which have been suggested to play a protective role in colorectal cancer development in laboratory and animal studies. Human studies have not shown consistent results. We examined the association between intakes of fish and n-3 fatty acids from fish and colorectal cancer risk in men enrolled in the Physicians' Health Study. Methods: The Physicians' Health Study began as a randomized trial to examine the effect of aspirin and B-carotene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 63 publications
7
117
1
8
Order By: Relevance
“…None of these measures of fat intake were associated with the risk for colorectal cancer, which is consistent with the results of several other prospective studies, [20][21][22] although some have reported a reduction in risk in association with a high intake of n À 3 fatty acids or a high ratio of n À 3 to n À 6 polyunsaturated fatty acids. 23,24 Strengths of this study are that dietary intakes were measured prospectively by food diaries using similar methods in the seven contributing studies, and that we were able to allow for the influence of several potential confounding factors. The main limitation is the size of the study; with 565 cases and 1,951 controls, we had ample power to detect moderate or large associations, but power was limited to detect small associations and was insufficient to examine anatomical subsets of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…None of these measures of fat intake were associated with the risk for colorectal cancer, which is consistent with the results of several other prospective studies, [20][21][22] although some have reported a reduction in risk in association with a high intake of n À 3 fatty acids or a high ratio of n À 3 to n À 6 polyunsaturated fatty acids. 23,24 Strengths of this study are that dietary intakes were measured prospectively by food diaries using similar methods in the seven contributing studies, and that we were able to allow for the influence of several potential confounding factors. The main limitation is the size of the study; with 565 cases and 1,951 controls, we had ample power to detect moderate or large associations, but power was limited to detect small associations and was insufficient to examine anatomical subsets of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A relative risk of 1?36 could be shown when women in the lowest quintile of red meat intake during adolescence were compared with women in the highest quintile. A shortened FFQ was used to examine the association between fish and n-3 fatty acid intake and colorectal cancer risk (30) . In the present study, a relative risk of 0?60 was shown for the highest v. the lowest category of fish intake.…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese population-based study, the n-3 PUFA (EPA, C 20 : 5n-3; docosapentaenoic acid, C 22 : 5n-3; DHA, C 22 : 6n-3) were associated with protection against developing hepatocellular carcinoma (22) , whereas another population-based prospective study undertaken by the Japanese Public Health Center demonstrated an inverse relationship between the intake of marine n-3 PUFA and the risk of colorectal cancer, even though the association was only significant in the proximal site of the colon (23) . Large studies, such as the European Prospective Investigation into Cancer and the United States' Physicians Health study, involving thousands of participants have confirmed the protection against cancer afforded by n-3 PUFA, particularly signifying a decrease in the risk of colorectal cancers (24,25) . In a case-control study, erythrocyte levels of EPA and DHA were inversely associated with breast cancer risk (26) .…”
Section: Dietary Fatty Acids and Cancer In Human Subjectsmentioning
confidence: 99%